Biofilm formation and its genes expressions in Staphylococcus epidermidis isolated from urinary tract infections of children in Isfahan - Samaneh Borooni; Vajiheh Nourbakhsh; Fahimeh Nourbakhsh; Elaheh Tajbakhsh; Afsaneh Yazdanpanah (International Archives of Health Sciences, 2019)
Aims: Staphylococcus epidermidis is an important bacterium, also one of the 40 species related to the Staphylococcus family. It can be found in the human normal body flora, commonly on the skin, and less commonly on mucosal flora. Instrument and Methods: In the cross-sectional study, we were isolated samples according to the laboratories standards, and S. epidermidis identification were collected for 1 year, 90 S. epidermidis from urinary tract infections of children were selected from educational hospitals in Isfahan, (Iran). In this way, we use the Kirby–Bauer method. S. epidermidis isolates were collected for determined biofilm producing method, with culturing in (Congo red agar) medium and microplate titration. Results: The results reveal that 45 methicillin resistance S. epidermidis isolates produce biofilm in different levels. The high resistance was for methicillin (50%), erythromycin (43.5%), ciprofloxacin (50.2%), and penicillin (46.9%). The lowest resistance was for linezolid (4%) and nitrofurantoin (5%). Conclusions: The results of our study show the high prevalence of antibiotic-resistant and biofilm producing of S. epidermidis strains, especially, in methicillin resistance S. epidermidis strains in the Isfahan hospitals, which could be a reservoir for antibiotic resistance genes.